ANALISIS FAKTOR YANG MEMPENGARUHI PENYALURAN PINJAMAN DANA TERHADAP KELAYAKAN KONSUMEN DI PT.MEGA AUTO FINANCE BATAM - Fitratul Anissa,; Putu Rani Susanthi, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This study aims to determine the character, capital, collateral, condition of economic, capacity and affect the eligibility of consumers in PT.Mega Auto Finance Batam. The type of research used is descriptive verification by describing and explaining the variables studied and then drawing conclusions. The object of research that becomes the independent variable is character(X1),capital(X2), collateral(X3),condition of econonmic(X4),capacity(X5) and consumer feasibility (Y) as the dependent variable. The population of this research is all prospective customers of PT.Mega Auto Finance Batam who want to apply for a loan of funds are 132 consumers. The sampling method used was accidental sampling, which is a sampling technique based on coincidence using the Slovin formula so that the sample in this study amounted to 65 people. The results showed the influence of character,capital,collateral,condition of economic,capacity on consumer eligibility. R Square 23.7% From these results it can be concluded that the character variables (X1), capital (X2), collateral (X3), contonoofecononmic (X4 ), capacity (X5) simultaneously influences the variables and consumer feasibility (Y) while 76.3% is influenced by other variables not examined in this study